Tablets im Unterricht deutscher Schulen - Eine empirische Studie zur Akzeptanz und Nutzung von Tablets in vier Schulen - Aufenanger, Stefan (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
In German schools tablets become an increasingly significant role, in which they either replace the traditional desktop computer or notebooks or be introduced as new digital media in the classroom. An empirical study at four schools in the city of Wiesbaden in Germany investigated the use of tablets in schools, expectations and acceptance of the new teaching with tablets by teachers and students as well as changes in the quality of teaching. The results show that the value of tablets dependent less of the devices than from their didactically justified use here is the educational.